Front Cover: Tuning the Carrier Transfer Behavior of Coaxial ZnO/ZnS/ZnIn2S4 Nanorods with a Coherent Lattice Heterojunction Structure for Photoelectrochemical Water Oxidation (ChemSusChem 23/2022). Issue 23 (18th November 2022) - Peng, Jing; Liu, Guorui; Jiao, Xianhui; Xia, Hongqiang; Li, Jing; Ma, Qingxiang; Jin, Jun; Li, Feng
Abstract : The Front Cover shows the coaxial "glove" structure of ZnO/ZnS/ZnIn2 S4 photoanode for efficiently photoelectrocatalytic (PEC) water splitting, which has a lattice‐matching interface like a "tightly connected puzzle" that can activate the carrier transport pathway. In addition, the PEC stability of the electrode is significantly improved because the ZnS/ ZnIn2 S4 encapsulation isolates ZnO from direct contact with the electrolyte. More information can be found in the Research Article by Jing Peng et al .